Human β‐defensin‐3 induces IL‐8 release and apoptosis in airway smooth muscle cells. Issue 9 (26th May 2017) - Wang, W.; Qu, X.; Dang, X.; Shang, D.; Yang, L.; Li, Y.; Xu, D.; Martin, J. G.; Hamid, Q.; Liu, J.; Chang, Y.
Summary: Background: Human airway smooth muscle cells (ASMCs) may have a pro‐inflammatory role through the release of inflammatory mediators. Increasing evidence indicates that human β‐defensins (HBDs) are related to pathogenesis of asthma. Objectives: To examine the plasma level of HBD‐1, HBD‐2 and HBD‐3 in asthmatic patients and the expression of their mouse orthologues in the lung tissue of a mouse model of chronic severe asthma. Further to investigate the effect of HBD‐3 on the release of the pro‐inflammatory cytokine IL‐8 and to explore the mechanisms. Methods: The plasma levels of HBD‐1, HBD‐2 and HBD‐3 from 34 healthy controls and 25 asthmatic patients were determined by ELISA. The expression of mouse β‐defensins MBD‐1, MBD‐3 and MBD‐14 in the lung tissue of asthmatic mice was detected by Western blot. The ASMCs were cultured with HBD‐3 for 24 hour, and then the supernatant level of IL‐8 was evaluated by ELISA and the cell viability was examined by WST‐1 assay. The signalling pathway was investigated with blocking antibodies or pharmacological inhibitors. Results: The plasma levels of HBD‐1 and HBD‐3 were elevated in asthmatic patients, and the expression of MBD‐14, the mouse orthologue for HBD‐3, was increased in asthmatic mice. HBD‐3‐induced IL‐8 production in a CCR6 receptor‐specific manner and was dependent on multiple signalling pathways. Moreover, HBD‐3‐induced cell apoptosis concurrently, which was dependent on the ERK1/2 MAPK pathway. Mitochondrial ROS regulated both HBD‐3‐induced IL‐8 production and cell apoptosis. Conclusions and Clinical Relevance: These observations provide clear evidence of an important new mechanism for the promotion of airway inflammation and tissue remodelling with potential relevance for the treatment of asthma.